Breeding programmes to improve male reproductive performance and efficiency of insemination dose production in paternal lines: feasibility and limitations - Miriam Piles; L. Tusell; Raquel Lavara; Manuel Baselga (World Rabbit Science, 2013)
This paper aims at reviewing the current genetic knowledge of the issues related to the efficient use of bucks in artificial insemination (AI). Differences between lines have been found relevant in semen production and quality traits not necessarily related to their specialization as maternal or paternal lines. Accurate heritability estimates indicate that genetic selection for increasing semen production by improving male libido and reducing the number of rejected ejaculates may not be effective. However, total sperm produced per ejaculate appears to be as an interesting trait to select for, despite that genetic correlation between ejaculate volume and sperm concentration has not been yet accurately estimated. Semen pH has shown low to medium heritability estimates and a low coefficient of variation, therefore it is not advisable to attempt improvement by direct selection. In general, sperm motility traits have shown low heritabilities but, the rate of motile sperms per ejaculate has been considered as convenient to select for. Morphological characteristics of the spermatozoa have revealed as medium to highly heritable. There are evidences of high genetic correlations between sperm traits before and after freezing-thawing. There are few studies regarding the estimation of heterosis of seminal traits but results indicate important and favorable direct and maternal heterosis in crosses between maternal lines. However, this has not been confirmed in a cross between two paternal lines. Until now, attempts to find parametric or non-parametric functions to predict ejaculate fertility through seminal characteristics recorded in routinely evaluations have been very unsatisfactory. Hence, it may be necessary to find other semen quality markers, or to evaluate some of the currently used ones in a more precise manner or closer to the AI time in order to improve the ability to predict ejaculate fertility. Several seminal characteristics phenotypically correlated to male fertility, could be considered as potential traits to select for in order to genetically improving this trait. However, only the semen pH has been checked for this purpose, and a negative result has been obtained. Other traits can be studied in the future but bearing in mind that the required experiments will need large number of bucks for an accurate estimation of the genetic correlation of the trait with male fertility. This means that these experiments will be expensive and difficult to set up. The most common criterion to select paternal lines, average daily gain, seems not to be genetically correlated to male fertility and seminal traits. Thus, selection for average daily gain has no detrimental consequences on these traits, and a multi-trait selection, including growth rate and seminal traits directly related to an efficient AI semen dose production, is feasible in paternal lines. The male contribution to fertility after natural mating and after AI with semen doses with high concentration is negligible, but it has been found that, under more restrictive conditions of AI, male contributions to fertility and litter size are low but higher in magnitude than the ones obtained after natural mating. The genetic correlation between the female and male contributions to fertility has been found to be moderate to high and positive.